Hegel on Physical Health and Illness: A Brunonian Influence and a Metaphysical Approach - Andrés Ortigosa (Ethics in Progress)
Physical health and illness according to Hegel is a topic that has been largely overlooked. To understand its importance in Hegel’s philosophy, one must first understand its medical context, which begins with the crisis of German medical theory in the late 18th and early 19th centuries. This crisis facilitated the entry of Brunonianism into German medicine. Hegel was influenced by this context but also introduced ideas of his own into his conception of health and illness. According to Hegel, health is related to fluidity and solidification, which are two metaphysical notions. Using the Brunonian vocabulary of his time alongside his own metaphysical framework, Hegel elaborated a metaphysical theory of physical health and illness.